Α‐Syntrophin stabilizes catalase to reduce endogenous reactive oxygen species levels during myoblast differentiation. (4th June 2017) - Moon, Jae Yun; Choi, Su Jin; Heo, Cheol Ho; Kim, Hwan Myung; Kim, Hye Sun
Abstract : α‐Syntrophin is a component of the dystrophin–glycoprotein complex that interacts with various intracellular signaling proteins in muscle cells. The α‐syntrophin knock‐down C2 cell line (SNKD), established by infecting lentivirus particles with α‐syntrophin shRNA, is characterized by a defect in terminal differentiation and increase in cell death. Since myoblast differentiation is accompanied by intensive mitochondrial biogenesis, the generation of intracellular reactive oxygen species (ROS) is also increased during myogenesis. Two‐photon microscopy imaging showed that excessive intracellular ROS accumulated during the differentiation of SNKD cells as compared with control cells. The formation of 4‐hydroxynonenal adduct, a byproduct of lipid peroxidation during oxidative stress, significantly increased in differentiated SNKD myotubes and was dramatically reduced by epigallocatechin‐3‐gallate, a well‐known ROS scavenger. Among antioxidant enzymes, catalase was significantly decreased during differentiation of SNKD cells without changes at the mRNA level. Of interest was the finding that the degradation of catalase was rescued by MG132, a proteasome inhibitor, in the SNKD cells. This study demonstrates a novel function of α‐syntrophin. This protein plays an important role in the regulation of oxidative stress from endogenously generated ROS during myoblast differentiation by modulating the protein stability of catalase. Abstract : α‐Syntrophin knock‐down muscle cells (SNKD) have a defect in differentiation. Excessive intracellular reactive oxygen species accumulated during differentiation of SNKD cells accompanied by a decrease of catalase. Degradation of catalase was rescued by MG132, a proteasome inhibitor. This demonstrates that α‐syntrophin plays an important role in the regulation of oxidative stress during myoblast differentiation by modulating the protein stability of catalase.